2015
DOI: 10.5717/jenb.2015.19.2.55
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unaccustomed downhill running on muscle damage, oxidative stress, and leukocyte apoptosis

Abstract: Kyung-Shin Park and Man-Gyoon Lee. Effects of unaccustomed downhill running on muscle damage, oxidative stress, and leukocyte apoptosis. JENB., Vol. 19, No. 2, pp.55-63, 2015 [Purpose] The purpose of this study was to investigate the effect of unaccustomed downhill running on muscle damage, oxidative stress, and leukocyte apoptosis.[Methods] Thirteen moderately trained male subjects performed three 40 min treadmill runs at ~70% VO2max on separate days: a level run (L) followed by two downhill runs (DH1 and DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Byrnes et al [193] reported smaller increases in plasma CK, plasma myoglobin and DOMS up to 48 h after a second DR bout when two 30 min bouts (slope: − 10%; intensity: 170 beats min −1 of heart rate recorded on level grade) were separated by 3-, 6-and 9-weeks. Further studies corroborated these results by reporting a lower leakage and/ or a faster clearance of intracellular muscle proteins in the blood [46,63,67,85,92,121,141,143,165,181,185], lower DOMS [63,68,85,92,121,141,143,185,192,196,197] and enhanced recovery of MVC force/torque [63] after a second DR bout (Table 1 and Fig. 3b).…”
Section: Prior Exposure To Downhill Runningsupporting
confidence: 60%
See 1 more Smart Citation
“…Byrnes et al [193] reported smaller increases in plasma CK, plasma myoglobin and DOMS up to 48 h after a second DR bout when two 30 min bouts (slope: − 10%; intensity: 170 beats min −1 of heart rate recorded on level grade) were separated by 3-, 6-and 9-weeks. Further studies corroborated these results by reporting a lower leakage and/ or a faster clearance of intracellular muscle proteins in the blood [46,63,67,85,92,121,141,143,165,181,185], lower DOMS [63,68,85,92,121,141,143,185,192,196,197] and enhanced recovery of MVC force/torque [63] after a second DR bout (Table 1 and Fig. 3b).…”
Section: Prior Exposure To Downhill Runningsupporting
confidence: 60%
“…3 a Schematic representation of the time course of alterations following downhill running (DR) and b current scientific evidence on the benefits of different adaptation strategies to DR (i.e. prior exposure to DR [46,63,67,68,85,92,121,141,143,165,181,184,185,192,193,196,197], preconditioning strategies [16,81], DR training [14,209,210,254], changes in stride pattern [32,67,68,218,219,221,220,228,255], the use of lower limb compression garments [15,236,237], and the use of specific footwear [28,149,253,256]. In a and b, orange, blue, red, purple, and green spheres correspond to isometric MVC force/torque loss, changes in running economy and mechanics, ultrastructural alterations, inflammation and oedema, and muscle soreness, respectively.…”
Section: Prior Exposure To Downhill Runningmentioning
confidence: 99%
“…We also measured oxidative stress (ie, d‐ROMs) and oxidative elimination ability (ie, BAP); however, these factors did not change over time and no significant difference was found between the CUR and PLA trials or between the experimental trials. In previous studies, oxidative stress markers significantly increased after whole body exercise, such as downhill running . One study reported that the product of oxidative stress was significantly suppressed by ingesting CUR .…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, any downhill running or walking may cause increased stress on the popliteus muscle and tendon [ 8 ]. High intensity exercise may induce a proteolytic pathway related to muscle damage and trigger inflammatory processes in the muscle [ 9 ]. The cause of the patient's condition was difficult to ascertain, but his hobby and walking habits could have resulted in enlargement and edema of the popliteus muscle.…”
Section: Discussionmentioning
confidence: 99%